Role of thermal photosynthetic plasticity in the dispersal and settlement of two global green tide formers: Ulva pertusa and U. ohnoi - Zanolla-Balbuena, Maríanela Fernanda; Carmona-Fernández, Raquel; Kawai, Hiroshi; Stengel, Dagmar B.; Altamirano, María (Springer Nature, 2019)
The green invasive macroalgae Ulva ohnoi and U. pertusa are known for their capacity to form green tides across many geographic regions. Given their global ecological and economic impact, photosynthetic responses of both Ulva spp. were tested in laboratory experiments using short-term (3 h, and 5 h) exposure to different temperatures (27–36 °C) and light regimes, simulating light deprivation during ballast water transport conditions. Heat treatment of ship’s ballast water has been widely advocated as a possible treatment to prevent biological contamination. In addition, the physiological performance of U. ohnoi was assessed in long-term experiments (14 days). We examined several photosynthetic parameters and physiological variables such as growth and pigment content as a measure of physiological fitness. Both species maintained stable values of Fv/Fm over several hours across temperatures, although Ulva ohnoi presented higher values of Fv/Fm, photosynthetic efficiency and NPQmax than U. pertusa, and activated dissipative protective mechanisms earlier. In the long-term experiment, U. ohnoi died by the 4th day at 36 °C. In surviving samples, Fv/Fm increased by day 7, regardless of temperature and decreased by day 14; lower values pertained to 34 °C. Photosynthetic efficiency of U. ohnoi decreased after 1 week at 27 and 29 °C, but at 31 and 34 °C, an increase was recorded after 7 days. The highest rETRmax was recorded at 29 °C, while growth optimum occurred at 27–31℃. We postulate that short-term thermal stress affects dispersal risk, which may also explain the seasonal replacement of the two Ulva spp. in Japan; and that U. ohnoi has a higher thermal tolerance that allows its settlement in new areas, resulting in a wide distributional range. Its physiological performance under the temperatures tested suggests that U. ohnoi may pose a greater risk of dispersal and settlement than U. pertusa.
Keywords: Algas; Green Tides; Invasive species; PAM; Ulva; Photosynthesis; Thermal plasticity